Confessions of a Murder Suspect - Patterson, James 1947-; Paetro, Maxine; Galvin, Emma. (New York : Hachette Audio, 2012)
Tandy Angel is, along with her brothers, a suspect in their parents' murder but having grown up under Malcolm and Maud Angel's perfectionist demands, Tandy decides she must clear the family name no matter what.
Unabridged.
Compact discs.
Read by Emma Galvin.
Keywords: Brothers and sisters -- Fiction; Twins -- Fiction; Perfectionism (Personality trait) -- Fiction; Family life -- Fiction -- New York (State); Secrets -- Fiction; Death -- Fiction; Mystery and detective stories; Audiobooks; New York (N.Y.) -- Fiction; Children's audiobooks